Clinical and imaging features of acute encephalopathy with biphasic seizures and late reduced diffusion in children - Zhang, M J (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2023)
Objective: To explore the clinical and imaging features of acute encephalopathy with biphasic seizures and late reduced diffusion(AESD) in children. Methods: For the case series study, 21 children with AESD from Peking University First Hospital, Provincial Children's Hospital Affiliated to Anhui Medical University, Children's Hospital of Fudan University, and Shanxi Children's Hospital who were diagnosed and treated from October 2021 to July 2023 were selected. Clinical data were collected to summarize their clinical information, imaging, and laboratory tests, as well as treatment and prognostic characteristics. Descriptive statistical analysis was applicated. Results: Of the 21 cases with AESD, 11 were males and 10 were females, with the age of onset of 2 years and 6 months (1 year and 7 months, 3 years and 6 months). Of the 21 cases, 18 were typical cases with biphasic seizures. All typical cases had early seizures within 24 hours before or after fever onset. Among them, 16 cases had generalized seizures, 2 cases had focal seizures, and 7 cases reached the status epilepticus. Of the 21 cases, 3 atypical cases had late seizures in biphasic only. The late seizures in the 21 cases occurred on days 3 to 9. The types of late seizures included focal seizures in 12 cases, generalized seizures in 6 cases, and both focal and generalized seizures in 3 cases. Diffusion-weighted imaging (DWI) test on days 3 to 11 showed reduced diffusion of subcortical white matter which was named "bright tree sign" in all cases. The diffuse cerebral atrophy predominantly presented in the front-parietal-temporal lobes was found in 19 cases between day 12 and 3 months after the onset of the disease. Among 21 cases, 20 had been misdiagnosed as autoimmune encephalitis, central nervous system infection, febrile convulsions, posterior reversible encephalopathy syndrome, acute disseminated encephalomyelitis, and hemiconvulsion-hemiplegia-epilepsy syndrome. All the cases received high-dose gammaglobulin and methylprednisolone pulse therapy with poor therapeutic effect. By July 2023, 18 cases were under follow-up. Among them, 17 cases were left with varying degrees of neurologic sequelae, including 11 cases with post-encephalopathic epilepsy; 1 recovered completely. Conclusions: AESD is characterized by biphasic seizures clinically and "bright tree sign" on DWI images. Symptomatic and supportive treatments are recommended. The immunotherapy is ineffective. The prognosis of AESD is poor, with a high incidence of neurological sequelae and a low mortality